Inovasi Pembelajaran Berbasis Proyek Kerajinan Bahan Plastik di SDN 05 Marisa - Muh Wahyuddin S. Adam; Cinta Bobihu; Sasri Ali; Ana Sisilia; Nur Dwi Nafan Dinata Rondjo; Nadia Lamanja (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to foster students' creativity in managing waste materials into useful items, with a focus on understanding abstract concepts through project-based learning (PBL) at SDN 05 Marisa, Grade VI. The approach used in this study is qualitative, with data collection techniques through group discussions and in-depth interviews with students and teachers. The research subjects consist of one class teacher and two students (one male and one female). The data obtained were analyzed using a qualitative method with a thematic analysis approach. The results of the study indicate that students felt excited and not surprised when asked to make crafts from recycled plastic, as they had previously experienced making crafts from other waste materials like ice cream sticks. Additionally, students understood the importance of recycling plastic, realizing that it can reduce plastic waste and create useful items. The teacher stated that the school had previously taught handcrafts using ice cream sticks, hot glue, and cardboard. This study provides insights into how project-based learning can enhance students' creativity, their understanding of the importance of recycling, and develop their practical skills in crafting with recycled materials.